2022
DOI: 10.3390/biomedicines10020366
|View full text |Cite
|
Sign up to set email alerts
|

Translational Implications of Dysregulated Pathways and microRNA Regulation in Quadruple-Negative Breast Cancer

Abstract: Triple-negative breast cancers (HER2−, ER−, PR−) continue to present a unique treatment challenge and carry unfavorable prognoses. The elucidation of novel therapeutic targets has necessitated the re-evaluation of stratification approaches to best predict prognosis, treatment response and theranostic and prognostic markers. Androgen receptor expression and function have important implications on proliferation, tumor progression, immunity and molecular signaling in breast cancer. Accordingly, there has been inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The versatility of miRNAs at physiological and pathological levels makes them indispensable factors for many types of cancer, including mammary cancers. This is corroborated by the fact that they have a function in racial cancer disparities based on diagnosis, prognosis, disease progression, and response to various therapeutic modalities 25 . For instance, mir-655 expression positively correlates with COX-2 in genetically diverse breast cancer cells grown as spheroids, thereby linking it with stem-like cells 26 .…”
Section: Discussionmentioning
confidence: 91%
“…The versatility of miRNAs at physiological and pathological levels makes them indispensable factors for many types of cancer, including mammary cancers. This is corroborated by the fact that they have a function in racial cancer disparities based on diagnosis, prognosis, disease progression, and response to various therapeutic modalities 25 . For instance, mir-655 expression positively correlates with COX-2 in genetically diverse breast cancer cells grown as spheroids, thereby linking it with stem-like cells 26 .…”
Section: Discussionmentioning
confidence: 91%
“…The versatility of miRNAs at physiological and pathological levels makes them indispensable factors for many types of cancer, including mammary cancers. This is corroborated by the fact that they have a function in racial cancer disparities based on diagnosis, prognosis, disease progression, and response to various therapeutic modalities (23). For instance, mir-655 expression positively correlates with COX-2 in genetically diverse breast cancer cells grown as spheroids, thereby linking it with stem-like cells (24).…”
Section: Discussionmentioning
confidence: 91%
“…Lehmann et al [40] have reported four similar subdivisions. Due to the fact that the LAR subcategory, which is unique in expressing androgen receptor (AR), is significantly different from the other three subcategories, AR-negative TNBCs have been grouped together in a category referred to as quadruple negative breast cancer (QNBC) [41][42][43]. As has previously been reported, ACSL4 overexpression is a defining characteristic of QNBC [24].…”
Section: Inverse Relationship Between Acsl4 Expression and Receptor E...mentioning
confidence: 99%